PENDAMPINGAN PENYUSUNAN SOAL BERORIENTASI HOTS BAGI PARA GURU SMA - Menggo, Sebastianus; Par, Leonardus; Gunas, Tobias; Guna, Stanislaus (Universitas Pendidikan Ganesha, 2021)
One of the focuses of education today is assessment oriented to the higher-order thinking skills. This skill encourages students could be able to think critically, analytically, systematically, particularly in the context of problem-solving, communicating, and collaborating with peers. However, not all educators have been able to construct the items test based on the skill needed. The purpose of this community service is to provide the knowledge related to the construction of item tests that oriented to the higher-order thinking skills of 45 Senior High School teachers.Â The methods used to achieve this objective were lecture, question answer, discussion, and presentation. The result showed the trainees understood the nature of the construction of the test-oriented to the higher-order thinking skill in the learning process. From the four meetings done, the trainees could be able to classify and construct the tests oriented to the lower-order thinking skill, medium-order thinking skill, and higher-order thinking skill.